WHISTLEBLOWING SEBAGAI ALAT PENCEGAH DAN PENDETEKSI FRUD : STUDI PADA BADAN PEMERIKSA KEUANGAN PROVINSI MALUKU - JULIE THERESYA PELAMONIA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
The level of corruption, collusion and nepotism that occurs in Indonesia every year megalami increase. This is characterized by increased fraud in government institutions both at the center and in the region so that action is needed from government personnel in terms of detecting and preventing fraud called whistleblowing and ethics. This study aims to find out the role of whistleblowing and professional ethics in the detection and prevention of fraud in one of the government agencies in ambon city. The method used is qualitative method using interview techniques with several informants from bpk maluku province who have experience as examiners The results showed that whistleblowing and professional ethics actions held by a government apparatus effectively detect and prevent fraud but the application has not been maximally implemented.